The theses for PhD degree - article Editorial (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
L.V. Tarasova – The role of nutritional deficiency of selenium, zinc and manganese in pathogenesis of chronic gastritis and duodenal peptic ulcer (evidence from Chuvash Republic).M.A. Morozova – Differential diagnosis of fever in patients with diffuse liver diseases.